Neodymium sorption on the Na-form of Transcarpathian clinoptilolite - Emilia T. Słota; Volodymyr O. Vasylechko; Zinoviy M. Yaremko; Svitlana R. Bagday; Olga Poddubnaya; Alexander M. Puziy (Heliyon, 2023)
The sorption properties of Na-modified Ukrainian Transcarpathian clinoptilolite towards neodymium aqueous solutions under dynamic conditions have been investigated. The sorption capacity of the Na-from of Transcarpathian clinoptilolite towards Nd(III) significantly depends on the concentration of neodymium salt, the pH of the solution, and the heat treatment temperature of the sorbent. Nd(III) is most efficiently sorbed from slightly alkaline solutions (pH 8.5), mainly by adsorption of neutral hydrolyzed forms of Nd(OH)3 on the surface of Na-clinoptilolite samples preheated at 75 °C. During the passage of an Nd(III) solution with a concentration of 1 μg mL−1 through the sorbent at a rate of 3 mL min−1 under optimal conditions, the sorption capacity of Na-clinoptilolite is 7.2 mg g−1, which is in 4 and 2.3 times higher than that of natural and acid-modified forms of this zeolite. It is shown that under the experimental conditions with an increase in the flow rate, the thickness of the stationary surface layer decreases, which leads to a decrease in the sorption capacity of Na-clinoptilolite. The best Nd(III) desorbents are solutions of mineral acids and acidified solutions of alkali metal salts (except NaCl), which provide 93–98 % extraction of lanthanide from the zeolite matrix. The method for neodymium trace amounts preconcentration from aqueous solutions in a solid-phase extraction mode with a further determination of this rare earth element by a spectrophotometric method was developed. The detection limit of this method is 0.75 ng mL−1 and the linearity was evaluated in the range of 2.5–500 ng mL−1.